Endoscopic hand suturing for mucosal defect closure after gastric endoscopic submucosal dissection may reduce the risk of postoperative bleeding in patients receiving antithrombotic therapy. Issue 1 (22nd June 2021) - Akimoto, Teppei; Goto, Osamu; Sasaki, Motoki; Mizutani, Mari; Tsutsumi, Koshiro; Kiguchi, Yoshiyuki; Takatori, Yusaku; Nakayama, Atsushi; Kato, Motohiko; Fujimoto, Ai; Ochiai, Yasutoshi; Maehata, Tadateru; et al.
Abstract : Objectives: Endoscopic hand suturing (EHS) is expected to decrease the risk of post‐endoscopic submucosal dissection (ESD) bleeding by closing mucosal defects. We investigated the efficacy of EHS after gastric ESD in patients with antithrombotic agents. Methods: In this prospective single‐arm trial, patients taking antithrombotic agents for cardiovascular disease, arrhythmia, cerebrovascular disease and/or peripheral arterial disease and having <3‐cm gastric neoplasms were recruited. The mucosal defects after ESD were closed by EHS in which the needle was delivered through an overtube, and the mucosal rim of the defect was continuously sutured in a linear fashion by manipulating the needle grasped with the needle holder, followed by cutting the remnant suture and retrieval of the needle. The primary endpoint was the incidence of postoperative bleeding within 4 weeks after ESD. Results: Twenty‐two lesions in 20 patients (continuing antiplatelet agents in 11, anticoagulant agents in eight, both in one) underwent ESD followed by EHS. All defects (median size, 30 mm; range, 12–51 mm) were completely closed by EHS and remained closed on postoperative day 3. The median number of stitches was six (range, 4–8) and median suturing time was 36 (range, 24–60) min. There were no adverse events during/after EHS or postoperative bleeding. Conclusions: Postoperative bleeding was not observed in patients taking antithrombotic agents without perioperative cessation. EHS appears to be useful for prevention of post‐gastric ESD bleeding in high‐risk patients. (Clinical registration number: UMIN000024184).